The Effectiveness of Effleurage Massage Accompanied with Consumption of Young Coconut Water (Cocos Nucifera L) to Relieve Pain Intensity in Women First Stage of Labor at the Madani Clinic, Manado City - Juwita, Noormah; Istiqamah, Istiqamah (Universitas Ibn Khaldun Bogor, 2024)
Childbirth is a process in which repeated contractions occur, which can cause Pain in the mother in labor. The Pain felt during labor can cause anxiety and fear, which will affect the birthing process. This research aims to determine the effectiveness of a combination of effleurage massage and consumption of young coconut water (Cocos Nucifera L) to reduce the intensity of Pain in mothers in the first stage of labor at the Madani Clinic, Manado City. The research design used was Quasi-Experimental. The population studied was all mothers giving birth in the Madani Clinic Working Area, Manado City. A sample of 13 people was obtained using the accidental sampling technique. The research instrument used was a questionnaire sheet. The research results were then analyzed using Man Whitney. The results of the analysis showed that there was no significant effect between the group given the combination intervention and the control group. Based on the research results, it is hoped that the research area will be able to include clinical midwives in acupressure therapy training, especially for women giving birth, so that it can relieve pain and increase comfort for women giving birth.